PENGARUH KEPEMILIKAN APLIKASI MOBILE BANKING DAN KONDISI EKONOMI ORANG TUA TERHADAP PERILAKU KONSUMTIF DI KALANGAN MAHASISWA FKIP UGJ CIREBON - Febianti, Yopi Nisa; Umaroh, Umaroh; Rusdiyana (FKIP Unswagati, 2023)
This study aims to determine whether there is an effect of ownership ofapplications mobile banking and the economic condition of parents on consumptive behavior among students of FKIP UGJ Cirebon. The research methodology used is a quantitative approach with a survey method. The population of this study were all active FKIP students with a sample of 71 students. Sampling technique using Accidental Sampling. Data collection techniques using a questionnaire and then data processing using SPSS software version 25.0. Data analysis used multiple linear regression. The results showed that there was a significant effect of ownership ofapplications mobile banking on consumptive behavior among FKIP students, this evidenced by the t-value of 7.677 which was greater than the t-table which was 1.99495 and the significance value of 0.000 was smaller than the error level of 0, 05. The economic condition of parents on consumptive behavior among FKIP students has a significant influence, this is evidenced by the t-value of 7.090 which is greater than the t-table which is 1.99495 and the significance value of 0.000 is smaller than the error level of 0.005. Ownership ofapplications mobile banking and the economic conditions of parents have a significant effect on consumptive behavior among FKIP students, as evidenced by the coefficient of determination of 0.681 or 68.1% while the rest is influenced by other factors. Thus, ownership ofapplications mobile banking and the economic condition of parents have a positive effect on consumptive behavior among students of FKIP UGJ Cirebon.